Minoriti Melayu di Bangkok dan kawasan sekitarnya: Antara survival dan kejayaan / Chaiwat Meesantan - Chaiwat, Meesantan (2017)
This study aims to investigate and explore the historical background, survival and success of Malay minority living with the Thai majority in Bangkok and its provinces during the Rattanakosin era; from the reign of king Rama I to the resettlement of prisoner of wars from Patani to Bangkok in 1786 up to the present time. This study adapts multi-disciplinary approach. The central plains region of Thailand, especially Bangkok and its surrounding areas, became intensely populated with people coming from different cultural backgrounds, including the Malay community with an estimated number of 700,000 people. The Malays had inhabited this area since the ruling of the Kingdom of Ayuthaya around 14th to 15th century and massive growth was evident since the early Rattanakosin era in the 18th century; much to the impact of war between the Kingdom of Siam and the Malay Kingdoms in the south. The findings of this study revealed that the Siamese government’s policies were the major factor that had greatly affected the survival of the Malays and the Malay community living particularly in central Thailand. The implementation of Siamese government policies had conveniently forced the Malays to adapt and conform to the policies for survival. King Rama during the Rattanakosin era had introduced various government policies that had affected the Malay’s way of life particularly under the assimilation policy. As a nation who aspired to maintain a strong national identity, the Malays had nevertheless adopted policies and modification of identity from time to time during the reign of King Rama. This life modification was performed for the sake of survival under the ruling of Rattanakosin. Their survival in every era consisted of different modifications; i.e. separation, adaptation, integration and assimilation. Their success was portrayed mainly through family and religious institutions during the Rattanakosin monarchial reign and further progressed to education, economy and political institutions during the Thailand democratic era. After 1906, the Malays in Bangkok and its surrounding areas had assumed their rights in the same manner with the Thai majority, without hindrance and any barrier to success in life. The successful Malay individuals pointed out several key factors that had enabled them to succeed. Among them were the background of parents, persevarance, level of education, creativity, and finally employment and income. At present, the Malays still possess all the rights to preserve their identity and to compete fairly within the majority Thai community for success.